PARADIGMA INTEGRASI-INTERKONEKSI DALAM EKONOMI ISLAM - Ali Muhayatsyah; Yoesrizal M Yoesoef (Faculty of Islamic Economics and Business, IAIN Lhokseumawe, 2018)
The process of Islamization is a methodological problem. Methodologically economics (social science) has a dependence on natural science. In other terms Islamic economic methodology is consultative and dynamic in order to produce transcendent knowledge supported by empirical and rational truths, as well as the main truths originating from God.The integration- interconnection paradigm is essentially that Islamic Economics should be inherent and not desirable because it can be integrated and interconnected with various scientific fields. Integration is done by making the Qur'an and hadith the grand theory of knowledge. Integration referred to here is related to efforts to integrate economic science with Islam without having to eliminate the uniqueness between the two sciences. Keywords: Integration, Interconnection, Islamic Economics.